Models, methods, and technologies for calculation of characteristics of the physical facility Uragan-2M - Martynov, S.O.; Luchaninov, O.O.; Lukyanova, V.P.; Khazhmuradov, M.A.; Prokhorets, S.I. (Вопросы атомной науки и техники, 2021)
Models, methods, and algorithms for three-dimensional modeling of the screw winding of the Uragan-2M torsatron are considered. The application of the method of kinematic modeling is substantiated as the most acceptable for obtaining solid-state and surface models of elements of a magnetic system. Methods for calculating the stresses and strains arising in the elements of the magnetic system of a screw winding under the influence of ponderomotive forces are presented, which makes it possible to determine the strength of the structural elements of the facility. Розглянуто моделі, методи і алгоритми тривимірного моделювання гвинтової обмотки торсатрона Ураган-2М. Обґрунтовано застосування методу кінематичного моделювання як найбільш прийнятного для отримання твердотільної і поверхневої моделей елементів магнітної системи. Наведено методи розрахунку напружень і деформацій, що виникають в елементах магнітної системи гвинтової обмотки під впливом пондеромоторних сил, що дає можливість визначити міцність елементів конструкції установки. Рассмотрены модели, методы и алгоритмы трехмерного моделирования винтовой обмотки торсатрона Ураган-2М. Обосновано применение метода кинематического моделирования как наиболее приемлемого для получения твердотельной и поверхностной моделей элементов магнитной системы. Приведены методы расчета напряжений и деформаций, возникающих в элементах магнитной системы винтовой обмотки под воздействием пондеромоторных сил, что дает возможность определить прочность элементов конструкции установки.